Merrill-Palmer quarterly (Wayne State University Press, 1982)
"Journal of developmental psychology."
Keywords: Families : Periodicals; Developmental psychology : Periodicals; Child development : Periodicals; Psychology, Child; Family; Psychology, Social; Famille : Périodiques; Psychologie du développement : Périodiques; Enfants : Développement : Périodiques; Rodzina; Rozwój psychofizyczny dziecka; Child development; Developmental psychology; Families; Ontwikkelingspsychologie